2021
DOI: 10.1177/1403494820987459
|View full text |Cite
|
Sign up to set email alerts
|

Nordic population-based study on internet use and perceived meaningfulness in later life: How they are linked and why it matters

Abstract: Aim: The aim was to explore the association between internet use, the use of specific internet-based activities and perceiving life as meaningful, among older adults in two regions in Finland and Sweden. Methods: The data was collected through a population-based survey ( N = 9386) as part of the GERDA project conducted in 2016. In order to analyse the associations between perceiving life as meaningful and internet use and related activities, odds ratios with a 95% confidence interval were calculated using bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Between-group comparisons in the study at hand revealed that after adjusting for potential covariates among variables measuring individual characteristics, socio-environmental factors and health status, internet use overall seems to be statistically significant only in the association to perceived meaningfulness, not to happiness nor life satisfaction. The results regarding the connection between internet use, internet activities and perceived meaningfulness in later life have previously been published (Viklund et al, 2021). However, the study at hand advances the previous study results by simultaneously exploring two other dimensions of subjective well-being in addition to perceived meaningfulness.…”
Section: Study Findingsmentioning
confidence: 57%
See 3 more Smart Citations
“…Between-group comparisons in the study at hand revealed that after adjusting for potential covariates among variables measuring individual characteristics, socio-environmental factors and health status, internet use overall seems to be statistically significant only in the association to perceived meaningfulness, not to happiness nor life satisfaction. The results regarding the connection between internet use, internet activities and perceived meaningfulness in later life have previously been published (Viklund et al, 2021). However, the study at hand advances the previous study results by simultaneously exploring two other dimensions of subjective well-being in addition to perceived meaningfulness.…”
Section: Study Findingsmentioning
confidence: 57%
“…A set of variables measuring individual characteristics (gender, age) and socio-environmental factors (study region, educational level, income level, marital status) are therefore included in the analyses related to this study. These variables are recoded, and the cut-off points for the recoding process are chosen in accordance with other scientific articles based on the GERDA study (e.g., Forsman et al, 2012;Viklund et al, 2021).…”
Section: Key Subjective Well-being Covariatesmentioning
confidence: 99%
See 2 more Smart Citations